Iberian markets reaction to goodwill and goodwill impairments - Maldonado, Isabel (2019)
This study aims to analyse in what extent goodwill and goodwill impairment losses are relevant to the market value of Iberian listed companies in the period from 2006 to 2015. The sample includes entities belonging to the PSI-20 index and the IBEX-25 index. Our results indicate that goodwill as a significative and positive relation with market value, but when considering the goodwill impairment, the analysis does not allow us to establish a relationship with market value. When activity sectors are considered, the industries Basic Materials and Utilities present a high relationship between market value and goodwill but regarding the relation between goodwill impairment and market value our results are inconclusive.